THEORETICAL AND METHODOLOGICAL PRINCIPLES OF THE LOGISTICS OF PALACEAND CASTLE TOURISM - TEPLIUK, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2024)
Palace and castle tourism is a kind of tourism that is rapidly gaining popularity in the world, particularly in Ukraine. This kind of cultural tourism is focused on visiting and studying historical and architectural monuments, such as palaces, castles, fortresses, monasteries and other objects of great historical, cultural and architectural value. It helps visitors to see unique historical objects, find out more about history and culture of the country, region or city where they are situated on. Moreover, palace and castle tourism boosts the local economy and cultural heritage.This article is aimed at the study of the theoretical and methodological basics of logistics in the palace and castle tourism. In this article the peculiarities of the logistical processes in the area of cultural heritage are analyzed, the importance of the implementation of logistics for the better tourist service and improving of the tourist flow management is set. Also, the issues of the preservation of Historical value of the objects, tourist flow management, using the IT in logistics and other aspects affecting the development of the palace and castle tourism are considered in this article. This work includes the analysis of the current trends in the tourist area, highlights challenges and obstacles in the implementation of logistics and shows the perspectives for future research. The research findings can be valuable for the members of the tourism industry, researchers and government structures that are involved in the development of the cultural heritage.The chosen topic has a high relevance in the modern world. The growing attention to the cultural heritage including palaces and castles provides new possibilities for the tourism industry. The development of logistics in this context becomes an important factor of the better tourist service and the improvement of the tourist flow management. The research of this topic boosts the development of the tourist.
Keywords: logistics; palace and castle tourism; cultural heritage; tourist flow; IT; management of logistical processes